Meningkatkan Penguasaan Kosakata Siswa melalui Permainan Edukatif Di SDN 2 Tiakur - Lekawael, Rosina Fransisca Joan; Lewier, Christian Albert; Meyer, Fredi (Gaba-Gaba : Jurnal Pengabdian Kepada Masyarakat dalam Bidang Pendidikan Bahasa dan Seni, 2024)
The Student Creativity Program (PKM) with the title “Improving Students' Vocabulary Mastery Through Educational Games at SD N 2 Tiakur” aims to improve the mastery of English vocabulary of grade 4 and 5 students through educational game-based learning methods. The educational games implemented, such as Word Bingo, Charades, and Memory Match, proved to be effective in helping students remember and understand new vocabulary more easily and fun. In addition, this method also increases students' learning motivation and creates an interactive learning atmosphere. Teachers and students gave positive responses to this learning method, where teachers felt helped in improving the quality of teaching, and students became more enthusiastic in learning English. The positive impact was also felt by the surrounding community, especially parents who began to more actively support their children in the learning process at home. This program not only succeeded in improving students' vocabulary mastery but also contributed to improving the quality of English education at SD N 2 Tiakur. The results of this activity show that the educational gamebased learning approach can be used as an effective alternative method in teaching English in primary schools, especially in areas with limited access to education, such as in Southwest Maluku Regency.